Estudo químico das pétalas, folhas, cálices e sementes de Hibiscus sabdariffa L. - RODRIGUES, Adriana Costa (2017)
Hibiscus sabdariffa L. is a refreshing and astringent aromatic herb used in folk medicine as diuretic, digestive, anti-lipemic, antihypertensive and laxative. In the petals of this plant is reported the occurrence of polyphenols, and several studies have related these metabolites to the treatment of kidney, stomach, heart and neurodegenerative diseases. Much of the studies conducted with H. sabdariffa are limited to the ethanolic and aqueous extracts of the calyces, due to the large consumption in the form of tea. In this sense, the present work had as objective to evaluate the chemical profile of the different organs of the plant and the antioxidant potential, since this activity is related to the treatment of several pathologies, such as cancer, cardiovascular diseases, cerebral dysfunctions, degenerative diseases and processes inflammatory. Additionally, leishmanicidal activity was evaluated because ethnopharmacological data reported the use of leaves of tea in the treatment of leishmaniasis. Initially, calyces, leaves, petals and seeds were collected from wich the respective ethanolic extracts were prepared, followed by liquid-liquid extraction with solvents of increasing polarity. The extracts and fractions were submitted to phytochemical prospecting using thin layer chromatography and several chemical developers, and it was possible to suggest the presence of steroids, terpenoids, saponins, propylpropanoids, phenylpropanoids and flavonoids. In the assay to evaluate the antioxidant activity, it was possible to observe that the fractions nbutanol (EC50 64.3 ± 6.2 μg mL–1) and ethyl acetate (EC50 69.3 ± 8.2 μg mL–1) showed the best results, which may be justified by the higher amount of total phenols (61.5 ± 2.8 and 30.7 ± 1.7 mg GAE/g sample, respectively). In the assay for evaluation of leishmanicidal activity, it was observed that the n-hexane fractions of the leaves (IC50 40 ± 8 μg mL–1), petals (IC50 83 ± 16 μg mL–1) and calyces (IC50 67 ± 8 μg mL–1) showed selectivity indexes of 0.37, 0.66 and 0.16, respectively. The ethanolic extract of the seeds was submitted to the analysis by gas chromatography coupled to mass spectrometry being possible to observe the presence of a series of esters (methyl hexadecanoate, ethyl hexadecanoate, methyl octadeca-9,12-dienoate, methyl 9-octadecenoate, methyl octadecanoate, ethyl octadeca-9,12-dienoate, ethyl 9-octadecenoate and ethyl octadecanoate) and fatty acids (hexadecanoic acid and octadeca-9,12-dienoic acid) of long chains, thus contributing to the knowledge of the chemical profile of this plant that has wide application in traditional medicine.